A 6G Techno-Economic Framework for evaluating the feasibility of the proposed technology enablers and business models - Dimitris Kokkinis; Nikos Ioannou; Dimitris Katsianis; Dimitris Varoutas (International Telecommunications Society (ITS), 2023)
The last years have witnessed a surge in research papers focusing on the visions, enabling technologies, use cases, business models, and applications of 6G Wireless Communications Networks. While the technological advancements have garnered significant attention, the technoeconomic feasibility of these proposed solutions remains unanswered. Due to the performance improvements over 5G and the necessary network densification, the implementation of a new 6G network is anticipated to incur significant infrastructure expenses. However, these expenditures can be reduced with careful planning and a smooth transition from 5G to 6G. It is crucial to study this transition and the interplay between parameters such as anticipated technologies, applications, services, business models, and policies to ensure the affordability of 6G systems. This research aims to provide a first, comprehensive technoeconomic framework capable of evaluating proposed technologies, use cases, and business models for the evolution of 6G wireless communications, in comparison to 5G deployments. The framework seeks to address fundamental questions such as the cost-effectiveness of adopting specific technologies in the deployment phase and the feasibility of proposed business models in terms of revenue generation and demand assumptions. Such knowledge is invaluable to researchers, engineers, regulators, and other industry actors as it enables quantification and assessment of different 6G deployments and investments. Additionally, it paves the way for an open, cross-industry dialogue on the economic prospects of 6G within a clear framework. Assessing various technology combinations prior to the standardization of 6G offers a significant advantage in terms of globally economical, high-capacity, and low-latency road mapping for broadband access. By developing a technoeconomic framework that considers both technical and economic aspects, this research contributes to the understanding and planning of 6G networks. The framework aids in the evaluation and selection of technologies and business models that align with cost-effective deployment strategies. Ultimately, it enables stakeholders to make informed decisions regarding the future development and deployment of 6G wireless communication networks.
Keywords: 330; 6G mobile communication; Business models; Techno-economic analysis; 5G mobile communication; Technology enablers; Feasibility